2020
DOI: 10.1111/aji.13220
|View full text |Cite
|
Sign up to set email alerts
|

Fertility factors affect the vaginal microbiome in women of reproductive age

Abstract: Problem For women of reproductive age, achieving a successful pregnancy requires both the normal functioning of reproductive endocrine and the health of the reproductive tract environment. We aimed to study how these fertility factors, such as female age, baseline sexual hormone levels, tubal patency, and vaginal pH, affect the composition of vaginal microbiome. Method of study The 16S rRNA sequencing was carried on vaginal microbiome samples from 85 women of reproductive age without vaginal infections or repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 57 publications
(88 reference statements)
0
28
0
Order By: Relevance
“…Animals in group 1 received seven daily applications of a sucrose gel vaginally, while animals in group 2 received seven daily applications of the gel alone. Since hormonal levels can influence VM composition ( 24 , 26 , 27 ), animals were administered an oral contraceptive for 21 days (1 month prior to sucrose treatment) to synchronize the menstrual cycles of the animals ( Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Animals in group 1 received seven daily applications of a sucrose gel vaginally, while animals in group 2 received seven daily applications of the gel alone. Since hormonal levels can influence VM composition ( 24 , 26 , 27 ), animals were administered an oral contraceptive for 21 days (1 month prior to sucrose treatment) to synchronize the menstrual cycles of the animals ( Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that this bacterium was more commonly found in the vagina of younger women or women with normal ovarian function. Meanwhile, the relative abundances of genera Varibaculum, Streptococcus, and Veillonella were positively related to age, indicating that the colonization of these bacteria in the vagina may increase with female age [33]. In another study Nasioudis et, al. mentioned that there are no statistically signi cant associations between the relative abundance of any bacterial taxa and maternal age, gestational age at birth, or neonatal gender [34].…”
Section: Discussionmentioning
confidence: 92%
“…It has previously been reported that host genetics, ethnicity, hormonal stage (e.g. menstruation cycle, menopause, pregnancy), sexual behaviour, and hygiene practices, amongst others factors, influence vaginal microbiota composition [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%